Map of part of North-West Territory shewing the locality of the Half-Breed Rebellion
This map shows the geographic area of the uprising by the Métis people from 1885, known as the North-West Rebellion, or Half-Breed Rebellion. Scale 1:2,154,240, or 34 miles to 1 inch. Relief shown by hachures. Shows The Canadian Pacific Railway, roads, trails and telegraph lines. Includes distance table. Inset: Reduced map shewing route to Winnipeg and North-West via Canadian Pacific Railway. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .